Can Hearts and Minds Be Bought? The Economics of Counterinsurgency in Iraq - Berman, Eli; Shapiro, Jacob N.; Felter, Joseph H. (Journal of Political Economy, 2011)
JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.